2022
DOI: 10.4028/p-5r7g9d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Electrophoretic Deposition (EPD) Voltage on SOFC Interconnect Morphology

Abstract: Solid oxide fuel cell has become one of the interest in the sustainable energy field. In order to improve the efficiency of a solid oxide fuel cell (SOFC), the interconnect must be coated with a protective coating of (MnCO)3O4 spinel coated stainless steel. Commercial manganese cobalt (MnCO)3O4 was used as a protective coating on ferritic stainless steel in this study using the electrophoretic deposition (EPD) coating technique. This article examines the impact of voltage deposition towards morphological chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…[19][20][21][22] Mn-Co spinel coatings have been developed using various methods, including pack cementation, 23 physical vapor deposition, 24 electrodeposition, 25 plasma spraying, 26 magnetron sputtering, 27 and electrophoretic deposition. 28 Adding reactive element oxide particles like La 2 O 3 , ZrO 2 , and Y 2 O 3 to spinel coatings improves their adhesion to the substrate and enhances protective properties against oxidation at high temperatures. [29][30][31] Regarding the effect of cerium oxide particles on spinel coatings, You 32 et al demonstrated that despite reducing the area specific resistance (ASR) of 430 stainless steel interconnect plates, the spinel coating NiFe 2 O 4 has little effect on the growth of chromia scale.…”
mentioning
confidence: 99%
“…[19][20][21][22] Mn-Co spinel coatings have been developed using various methods, including pack cementation, 23 physical vapor deposition, 24 electrodeposition, 25 plasma spraying, 26 magnetron sputtering, 27 and electrophoretic deposition. 28 Adding reactive element oxide particles like La 2 O 3 , ZrO 2 , and Y 2 O 3 to spinel coatings improves their adhesion to the substrate and enhances protective properties against oxidation at high temperatures. [29][30][31] Regarding the effect of cerium oxide particles on spinel coatings, You 32 et al demonstrated that despite reducing the area specific resistance (ASR) of 430 stainless steel interconnect plates, the spinel coating NiFe 2 O 4 has little effect on the growth of chromia scale.…”
mentioning
confidence: 99%